2021
DOI: 10.1093/mutage/geab030
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mutations induced by cold atmospheric plasma jet treatment relative to known mutagens in Escherichia coli

Abstract: The main bactericidal components of cold atmospheric plasma (CAP) are thought to be reactive oxygen and nitrogen species (RONS) and UV radiation, both of which have the capacity to cause DNA damage and mutations. Here, the mutagenic effects of CAP on Escherichia coli were assessed in comparison to X- and UV-irradiation. DNA damage and mutagenesis were screened for using a diffusion-based DNA fragmentation assay and modified Ames test respectively. Mutant colonies obtained from the latter were quantitated and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The mutagenicity of cold atmospheric plasma by the Ames test has been explored to a lesser extent. In a study by Patenall et al (2021) [30], a modified Ames test using E. coli strains WP2 was conducted. The results showed that mutations in the bacteria were significantly induced by exposing them to helium plasma for longer durations (10 min).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutagenicity of cold atmospheric plasma by the Ames test has been explored to a lesser extent. In a study by Patenall et al (2021) [30], a modified Ames test using E. coli strains WP2 was conducted. The results showed that mutations in the bacteria were significantly induced by exposing them to helium plasma for longer durations (10 min).…”
Section: Discussionmentioning
confidence: 99%
“…However, the preparation of test substances in our study could not follow this guideline since they were not solid or liquid test substances. Hence, the protocol for plasma exposure was modified from a previous study by Patenall et al, 2021 [ 30 ]. Additionally, Mortelmansit and Zeiger, 2000 [ 31 ], recommended that for general screening purposes, a tier approach should be used using strains TA98 and TA100 with or without metabolic activation to ensure that mutagens with different mechanisms of action can be detected.…”
Section: Methodsmentioning
confidence: 99%
“…RONS are known signaling factors that can directly involve in cell proliferation and differentiation by activating proteins or indirectly participate in cell proliferation and differentiation by changing the redox state of cells 97,98 . Although the details of the action of ARTP on DNA in living cells and the molecular mechanism of the subsequent mutation are still unclear, it can be determined that oxidized DNA damage caused by various RONS generated in plasma and their chemical reactions is important in the mutation process after probing the properties of ARTP and the diagnosis of the reactive species 99 . In summary, ARTP technology has broad application prospects in the field of microbial strain mutagenesis breeding 100 …”
Section: Artpmentioning
confidence: 99%
“…In the presence of ROS, RNS, and UV in the CAP, there is bacterial mutation to produce antioxidant-resistant strains. However, the ability of ROS and RNS to induce mutation is average (Patenall et al 2021 ) and the amount of UV is low, so the actual formation of mutagenic resistant bacteria is low. The formation of survival bacteria is largely dependent on the alteration of the bacterial phenotype.…”
Section: The Causes Of Survival Bacteria Formation In Capmentioning
confidence: 99%